2020
DOI: 10.1111/cogs.12918
|View full text |Cite
|
Sign up to set email alerts
|

A Principled Approach to Feature Selection in Models of Sentence Processing

Abstract: Among theories of human language comprehension, cue‐based memory retrieval has proven to be a useful framework for understanding when and how processing difficulty arises in the resolution of long‐distance dependencies. Most previous work in this area has assumed that very general retrieval cues like [+subject] or [+singular] do the work of identifying (and sometimes misidentifying) a retrieval target in order to establish a dependency between words. However, recent work suggests that general, handpicked retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…While many studies that have reported facilitatory interference tested sentence grammaticality, our results, along with Cunnings and Sturt (2018), indicate that similar effects arise because of plausibility. Cunnings and Sturt claimed that semantic interference arises because readers utilize the lexical properties of verbs, such as [drinkable] for the verb drink , as retrieval cues (see also Smith & Vasishth, 2020; Van Dyke & McElree, 2006). Our results are compatible with this claim for L1 language comprehension and extend it to L2 comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies that have reported facilitatory interference tested sentence grammaticality, our results, along with Cunnings and Sturt (2018), indicate that similar effects arise because of plausibility. Cunnings and Sturt claimed that semantic interference arises because readers utilize the lexical properties of verbs, such as [drinkable] for the verb drink , as retrieval cues (see also Smith & Vasishth, 2020; Van Dyke & McElree, 2006). Our results are compatible with this claim for L1 language comprehension and extend it to L2 comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, which features can actually modulate processing and why, and whether the same set of features acts as cues cross-linguistically are still debated open questions (Smith & Vasishth, 2020; see also Mertzen et al, 2020). Finally, top-down models such as the one proposed by Chesi (2015) and Chesi and Canal (2019) also assign an important role to morphosyntactic features, since they can either increase or mitigate the cost involved to Biondo, N., Pagliarini, E., Moscati, V., Rizzi, L., & Belletti, A.…”
Section: The Role Of Structure and Morphosyntactic Features: The Psyc...mentioning
confidence: 99%
“…Since we now deal with self-paced reading, in which readers have no look-ahead possibility, it is assumed that no upcoming words are used as context cues (see 18-a). For the wh-recall, only the syntactic category of the wh-dependent is used as a cue to increase spreading activation (more could be added; see Arnett & Wagers, 2017;Kush, 2013;Kush et al, 2015;Patil, Vasishth, & Lewis, 2016;Parker & Phillips, 2017;Smith & Vasishth, 2020 for investigations of what features are relevant for cue-based retrieval).…”
Section: Retrieval From Declarative Memorymentioning
confidence: 99%